PENERAPAN EARLY WARNING SCORE (EWS) SEBAGAI DETEKSI MORTALITY - Wardah Fauziah; Novian Mahayu Adiutama (Journal Keperawatan, 2023)
EWS is based on an assessment of changes in the patient's condition through systematic observation of all the patient's physiological changes so as to avoid unexpected events in the emergency room or the Intensive Care Unit room. Patient deterioration can occur when the evaluation and implementation of EWS are not in accordance with the algorithm. This study aims to determine the results of EWS implementation as mortality detection. This type of research is quantitative with a quasy experimental method with a pretest-posttest design with a control group. The sample used in this study were inpatients in the adult room with a total of 275 people taken by accidental sampling technique. Respondents who had been given the intervention continued with measuring early death using the Gross Death Rate (GDR). Based on the results of research and analysis of statistical tests that have been carried out on the application of EWS, the results obtained are a p-value of 0.028 (p <0.05) so that it can be concluded that the application of EWS has an effect on patient GDR. As early death detection, the intervention group is lower than the control group. These results significantly reduced the GDR and ADR in the intervention group compared to the control group.